Pyla-Koutsopetria Archaeological Project: Excavations at Pyla-Vigla in 2022 - Olson, Brandon R.; Landvatter, Thomas; Stephens, Justin; Scott Moore, R. (Journal of Hellenistic Pottery and Material Culture, 2022)
Pyla-Vigla (Vigla), investigated as part of the Pyla-Koutsopetria Archaeological Project (PKAP), is a fortified settlement dating to the early Hellenistic period ca. 325–275 BCE. The site is located in southeastern Cyprus on the primary overland route between ancient Kition and Salamis (figs. 1–3). The largely ephemeral (ca. 50 year) nature of Vigla’s occupation presents a valuable opportunity to shed light on a poorly understood period of ancient Cyprus. The early Hellenistic period saw the island transition from a political system based on semi-autonomous city kingdoms to the incorporation into an incipient imperial system. With a sound stratigraphic profile consisting of multiple undisturbed floor and subfloor levels, a homogeneous material assemblage, and discrete chronological benchmarks, Vigla represents an ideal case study to explore the imperial mechanisms of the earliest Hellenistic kings. These mechanisms were devised both to subjugate the island of Cyprus and to carve out their own spheres of influence within the remnants of Alexander the Great’s empire during the late fourth and third centuries BCE.